PTH-082 Dysregulation of a novel axis of epithelial-T-cell interaction is evident in IBD. (June 2019) - Dart, Robin; Vantourout, Pierre; Irving, Peter; Hayday, Adrian
Abstract : Introduction: Although epithelial dysfunction is an early initiating factor in inflammatory bowel disease (IBD), the role of the specialised intraepithelial immune compartment in this process remains unknown. Our research group has previously demonstrated that a subset of intraepithelial T cells expressing the γδ T cell receptor are selectively regulated by self-encoded molecules restricted to the epithelium known as Butyrophilin-like (BTNL) proteins (Di Marco Barros et al Cell 2016). Here we investigate whether this selective regulation of human γδ T cells is perturbed in the dysregulated epithelium of IBD and the factors which may contribute to this. Methods: A short-term whole gut explant culture was used to isolate γδ T cells from colonic biopsies obtained at endoscopy from donors, facilitating flow-cytometric phenotyping and functional studies. Results: In the majority of non-IBD controls, co-culture of colonic lymphocytes with HEK293T cells co-transduced with intestine specific BTNL3+BTNL8 proteins, resulted in profound TCR down-regulation in a subset of γ&obar;T cells (specifically those expressing the Vγ2/3/4 chains). αE β7 is a lymphocyte marker of epithelial residence present on the vast majority of γ&obar;T cells in health. αE β7+ γ&obar;T cells make TCR down-regulation responses to BTNL3+8, whereas the subset of γ&obar;T cell αE β7− cells, which are in the minority, had grossly attenuated or absent assay responses. In many IBD patients, there is significantly reduced αE β7 expression on γ&obar;T cells, and a severe attenuation or loss of BTNL-dependent TCR down-regulation. To assess whether the inflammatory milieu of IBD contributes to this dysregulation; addition of pro-inflammatory cytokines IL-12 and IL-18 (but not IL-1β and IL-23) to an organ culture system lead to down regulation of αE β7 on γ&obar; T cells and a consequent attenuation of response to BTNLs. This clearly implicates specific cytokines in the disruption of the γ&obar;-BTNL axis which is evident in disease. Further characterisation of αE β7−γ&obar;T cells demonstrated an activated pro-inflammatory phenotype in comparison to more quiescent αE β7+ γ&obar;T cells. Conclusion: The BTNL-γ&obar;T cell axis, is a novel and important mechanism by which epithelial cells and a specific subset of the intraepithelial γ&obar;T cell compartment communicate, and is often dysregulated in IBD. While our data suggests that IL-12 blockade may help to restore this axis, IL-23 may be redundant in this setting, with implications for emerging therapeutic strategies. αE β7 is a current target of therapeutic blockade, which has the potential to disrupt this axis and ultimately may exacerbate disease given the pro-inflammatory nature of αE β7−γ&obar;T cells.